THE CARACTERIZATION THE CARACTERIZATION OF SIMPLISIA AND EXTRACT OF CLOVE LEAVES (Syzigium aromaticum Merr. Et Perry L) FOR HERBAL MOUTHWASH ACTIVE INGREDIENS - Wirnawati Wirnawati; Ika Ayu Mentari; Nur Sholeh Aryodi Pernando (Jurnal Ilmu Kesehatan, 2020)
One of the oral and dental diseases that is often experienced by most people is dental caries. Clove leaves (Syzygium Aromaticum Merr. Et Perry L) have compounds that can prevent the activity of the bacterium Streptococcus mutans which is the cause of dental caries. This research is non experimental which focuses on the characterization of clove leaves. Characterization of simplisia and sample extracts include organoleptic observation, microscopy, phytochemical screening using Thin Layer Chromatography (TLC), determination of soluble substances in certain solvents (ethanol and water), total ash content, water soluble ash content, insoluble ash content in acid, then drying shrinkage test. The results of the organoleptic test for simplisia and extract of clove leaf showed that they have a dark brown color, specific aromatic odor, spicy and bitter taste. Clove leaf extract has a brownish black color, aromatic odor and has a bitter and pungent taste. Microscopic test of simplisia of clove leaves showed that there was a mesophyll includes palisade tissue, with calcium oxalate crystal, anomistic type stomata, identification fragments are fragments of the lower epidermis with stomata. The results of the percentage of soluble substances of simplisia and ethanol extract of clove leaf were 50% and 40%, the percentage of soluble substances of simplisia and ethanol extract of clove leaf were 1.73% and 4.33%. The percentage of total ash content of simplisia and ethanol extract of clove leaf 11.4% and 22%, the percentage of water soluble ash content of simplisia and extract was 16.9%, 17.5%. Percentage of insoluble ash content of simplisia acid and extract 9.5% and 10.5%. Shrinkage of simplisia and extracts were 7.6% and 11.46%.